Estimation of genetic variation of Amorphophallus titanum Becc. based on Random Amplified Polymorphic DNA (Biodiversitas Journal of Biological Diversity, 2008)
Amorphophallus titanum Becc. (Araceae), is known by titan arum (western) or bunga bangkai (Indonesian), is the bulkiest inflorescence in the world. The species is valued for its unique character of their inflorescence. The species has been overexploited and is considered as vulnerable plant species. The present study is carried out to assess genetic diversity and to estimate genetic relationship among 22 accessions collected from two different populations in Sumatra using Random Amplified Polymorphic DNA (RAPD). Nine RAPD primers generated 143 scorable bands which 137 (95.84%) of them were polymorphic. Clustering analysis was performed based on RAPD profiles using the UPGMA method. The range of genetic dissimilarity value among accessions was from 0.14 to 0.59, while the range of genetic dissimilarity among populations was from 0.67 and 0.77. These values showed that A. titanum from Sumatra were more genetically diverse among genotypes than that of among populations.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Amorphophallus titanum Becc. random amplified polymorphic DNA.